Internalisasi Nilai-Nilai Multikultural dalam Kurikulum Pendidikan Agama Islam di Indonesia: Penelitian - Muhammad Nasrullah Ramadhana; Febby Adinda; Nurhaflisma Lubis; Burhanuddin; Sapri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Indonesia is a multicultural nation characterized by high diversity in ethnicity, culture, religion, and social backgrounds. This diversity necessitates an educational approach, particularly in Islamic Religious Education (IRE), that extends beyond cognitive religious instruction to the cultivation of tolerant, inclusive, and moderate attitudes. This article examines the concepts, implementation, and challenges of internalizing multicultural values within the Islamic Religious Education curriculum in Indonesia. Employing a qualitative library research approach, data were collected from academic books, peer-reviewed journal articles, and relevant educational policy documents, and analyzed through content analysis. The findings reveal that multicultural values in IRE are firmly grounded in Islamic teachings, including tolerance (tasamuh), justice (al-‘adl), equality (musawah), and human brotherhood (ukhuwah insaniyyah). These values can be integrated into learning objectives, instructional materials, teaching methods, and assessment practices. However, the internalization of multicultural values in schools faces several challenges, such as curriculum limitations, teachers’ capacity and resistance, students’ social dynamics, and the influence of identity politics and the broader social environment. Therefore, systematic and sustainable efforts are required to strengthen the integration of multicultural values in the IRE curriculum to promote religious moderation and preserve national unity.